Genetic engineering as a powerful tool to improve probiotic strains. Issue 2 (3rd July 2017) - Bravo, Daniel; Landete, José M.
Abstract: Over the last decade, there has been increasing interest in the use of probiotic microorganisms. However, certain doubts have arisen around probiotics, because of the beneficial effects of these microorganisms are not clear yet, and in many occasions those beneficial effects have not been proven. Therefore, it would be of interest if these probiotic strains were able to acquire new attributes to allow them improve and increase their beneficial characteristics. Genetic engineering can be used for human applications; for instance, the resistance to antibiotics is removed and the probiotic bacteria are modified in its own DNA. This process can be achieved by: (1) the use of food-grade vectors derived from lactic acid bacteria and/or bifidobacteria cryptic plasmids, (2) the genes integration or deletion in the chromosome of the probiotic strain, by site-specific recombination using the attP/integrase system, or by homologous recombination, using either suicide vectors, (3) using the clustered regularly interspaced short palindromic repeats (CRISPR) and the CRISPR-associated (Cas) nuclease. Through genetic engineering, the knowledge of probiotic strains as well as its use could be improved, and the doubts about probiotics could be crumped.